PENINGKATAN HASIL BELAJAR MELALUI MODEL DISCOVERY LEARNING BERBANTU MEDIA AUDIOVISUAL PADA PEMBELAJARAN TEMATIK SISWA KELAS V TEMA 8 DI SDN NGURENREJO TAHUN PELAJARAN 2020/2021 - Melinda Pangestika; Choirul Huda; Joko Susanto (JS (JURNAL SEKOLAH), 2021)
Abstract : Improving Learning Outcomes Through Discovery Learning Learning Models Assisted by Learning Media in Thematic Learning of Class V Students Theme 8 at SDN Ngurenrejo Academic Year 2020/2021. PTK. Teacher Professional Education Study Program, Postgraduate Faculty, PGRI University Semarang. Advisory Lecturer Choirul Huda M.Si, M.Pd. The Civil Service Teacher Joko S.Pd, M.Pd. The background that drives this research is the learning outcomes of fifth grade students at SDN Ngurenrejo on the Second Semester Daily Examinations who achieve the Minimum Completeness Criteria (KKM) only 5 of 15 students. This is because students talk alone with their classmates so they don't focus on paying attention to the teacher when explaining the material. Students are only active when appointed by the teacher. The problem in this study is how to improve learning outcomes through the Discovery Learning learning model assisted by audiovisual media in thematic learning for Class V Theme 8 at SDN Ngurenrejo for the 2020/2021 academic year. This study aims to improve learning outcomes through the Discovery Learning learning model assisted by audiovisual media in thematic learning of class V theme 8 students at SD Negeri Ngurenrejo for the 2020/2021 academic year. This type of research is Classroom Action Research (CAR). The subject of this research is the learning outcomes of the fifth grade students of SDN Ngurenrejo, totaling 15 consisting of 8 male students and 7 female students. The object under study is the learning outcomes of students in thematic learning. The results showed that student learning outcomes in the first cycle the average value of learning outcomes was 65.33 with an average percentage of completeness of 53.5%. Then in the second cycle the average value of learning outcomes is 73.67 with an average percentage of completeness of 76.5%. In cycle III the average value of learning outcomes is 82.67 with an average percentage of completeness of 96.5%. Furthermore, it can be seen that in the first cycle to the second cycle there was an increase in the average value of 8.34 and the percentage of completeness by 23%. Then the increase in the average value from cycle II to cycle III is 9 and the percentage of completeness is 20%. It can be seen that in cycle II and cycle III have met the success indicators with the achievement of completeness in the second cycle of 76.5% and the third cycle of 96.5%. So it can be concluded that the application of the Discovery Learning model assisted by audiovisual media can improve learning outcomes in thematic learning of class V Theme 8 SD Negeri Ngurenrejo for the 2020/2021 academic yearKeywords: CAR, discovery learning, learning outcomesAbstrak : Peningkatan Hasil Belajar Melalui Model Pembelajaran Discovery Learning Berbantu Media Pembelajaran Pada Pembelajaran Tematik Siswa Kelas V Tema 8 Di SDN Ngurenrejo Tahun Pelajaran 2020/2021. PTK. Program Studi Pendidikan Profesi Guru Fakultas Pasca Sarjana Universitas PGRI Semarang. Dosen Pembimbing Choirul Huda M.Si, M.Pd. Guru Pamong Joko S.Pd, M.Pd. Latar belakang yang mendorong penelitian ini adalah hasil belajar siswa kelas V di SDN Ngurenrejo pada Ulangan Harian Semester II yang mencapai Kriteria Ketuntutasan Minimal (KKM) hanya 5 dari 15 siswa. Hal ini disebabkan siswa berbicara sendiri dengan teman satu bangku sehingga kurang fokus dalam memperhatikan guru ketika menjelaskan materi. Siswa hanya aktif ketika ditunjuk oleh guru. Permasalahan pada penelitian ini adalah bagaimana meningkatkan hasil belajar melalui model pembelajaran Discovery Learning berbantu 101 media audiovisual pada pembelajaran tematik Kelas V Tema 8 di SDN Ngurenrejo Tahun Pelajaran 2020/2021. Penelitian ini bertujuan untuk meningkatkan hasil belajar melalui model pembelajaran Discovery Learning berbantu media audiovisual pada pembelajaran tematik siswa kelas V tema 8 di SD Negeri Ngurenrejo Tahun Pelajaran 2020/2021. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK). Subjek penelitian ini adalah hasil belajar siswa Kelas V SDN Ngurenrejo yang berjumlah 15 yang terdiri dari 8 siswa laki – laki dan 7 siswa perempuan. Adapun objek yang diteliti adalah hasil belajar peserta didik dalam pembelajaran tematik. Hasil penelitian menunjukkan bahwa hasil belajar siswa pada siklus I nilai rata-rata hasil belajar yaitu 65,33 dengan rata-rata presentase ketuntasan sebesar 53,5%. Kemudian pada siklus II nilai rata-rat hasil belajar yaitu 73,67 dengan rata-rata presentase ketuntasan sebesar 76,5%. Pada siklus III nilai rata-rata hasil belajar yaitu 82,67 dengan rata-rata presentase ketuntasan sebesar 96,5%. Selanjutnya dapat diketahui bahwa pada siklus I ke siklus II terjadi peningkatan nilai rata-rata sebesar 8,34 dan presentase ketuntasan sebesar 23%. Kemudian peningkatan nilai rata-rata dari siklus II ke siklus III sebesar 9 dan presentase ketuntasan sebesar 20%. Dapat diketahui bahwa pada siklus II dan siklus III sudah memenuhi indikator keberhasilan dengan pencapaian ketuntasan siklus II sebesar 76,5% dan siklus III sebesar 96,5%. Maka dapat disimpulkan bahwa penerapan model Discovery Learning berbantu media audiovisual dapat meningkatkan hasil belajar pada pembelajaran tematik siswa kelas V Tema 8 SD Negeri Ngurenrejo Tahun Pelajaran 2020/2021.Kata Kunci : PTK, discovery learning, hasil belajar